The role of faith-based health professions schools in Cameroon's health system. Issue 6 (3rd June 2021) - Herzig van Wees, Sibylle; Sop Sop, Maturin Désiré; Betsi, Emmanuel; Olongo, Silvère Antoine; Jennings, Michael
ABSTRACT: Faith-based health professions schools contribute to the training of staff in many Sub-Saharan African countries. Yet little is known about these actors, their role in the health system, potential comparative advantages and challenges faced. This is a qualitative study drawing on 24 qualitative interviews and 3 focus group discussions. Participants included faith-based health professions schools, staff at faith-based health professions schools, Ministry of Health officials and donors. Thematic analysis was used to analyse the data. The findings reveal that understanding of faith-based health professions schools held by donors and the Ministry of Health rest on a set of assumptions rather than evidence-backed knowledge and that knowledge on key aspects is missing (not least on the market share of such actors). This suggests that collaboration with and oversight of these non-state schools is limited, raising questions about the balance of state regulation and control in the public-private mix for training health workers. Linked to this weak oversight, the findings also raise concerns over a number of problematic activities at these schools, unaccredited training programmes and the presence of missionary volunteers whose presence and actions are rarely interrogated.